“Efecto de cuatro dosis de micronutrientes en el cultivo de Pepinillo híbrido en American Slicer 160 F1 HYB, en la provincia de Lamas”. - Chupillón Cubas, Guin Jesús (2017)
The following research work titled as "Effect of four doses of micronutrients in the cultivation of hybrid cucumber Em American Slicer 160 F-1 Hyb, in the province of Lamas" was conducted in order to determine the optimal dose of secondary macronutrients and micro-nutrients (Ca, Mg, S, Zn, Fe, Mn, B, Cu, Micromate Calciuum Fortified) in growing cucumber (Cucumis sativus L.) Slicer hybrid American Hyb 160 F-1 and performing the treatment economic analysis studied. This research was conducted on the property of Mr. Jorge Luis Pelaez Rivera, located in the district and province of Lamas, San Martin department, a South Latitude 06 ° 20 '15' 'West Longitude 76 ° 30 '45' 'at an altitude of 835 m a. s. l. Statistical Design randomized complete block (RCBD) with four replications and five treatments was used. The variables evaluated were: percentage of germination, plant height (cm), fruit weight (g), fruit length (cm), fruit diameter (cm), number of fruits produced per plant, number of fruit per plant , fruit yield per plant and per hectare fruit yield (t ha-1) and economic analysis. The results indicate that the optimal dose was the T3 (75 kg ha-1 secondary macronutrients and micronutrients (Ca, Mg, S, Zn, Fe, Mn, B, Cu, Micromate Calciuum Fortified) treatment that generated the greatest yield per hectare, benefit have / economic and profit / Net (77,166.70 kg.ha-1, 0.78 y S/. 13,512.01). Keywords: Dose, secondary macronutrients, micronutrients, gherkin, performance, cost benefit, net profit.